Translanguaging as a Pedagogical Strategy for Enhancing Students' English Reading Comprehension - Azlya Alizara Dilrahman; Dedeh Rohayati; Lilies Youlia Friatin (Journal of English Education Program (JEEP), 2026)
This study investigates how translanguaging serves as a teaching strategy to improve students' English reading skills in higher education. The study aims to examine students' implementation and perspective on translanguaging in reading activities. Translanguaging refers to the application of all language skills in a flexible way to achieve comprehension in learning a foreign language. This research applied a qualitative method with a case study approach, and data were obtained through observations and interviews. The participants of this study were purposively selected, consisting of one class of first-year student, and one lecturer for observation. Six students and one lecturer were interviewed based on their level of participation in learning activities to triangulate the data and validate the opinions. The results of this study show that the implementation of translanguaging can improve comprehension in reading English. Students naturally applied translanguaging through discussion, note-taking, retelling, and expressing their understanding. They used Indonesian, Sundanese, and also multimodal, such as gestures. In addition, students gave a positive perspective on translation; they felt relaxed, motivated and more confident when reading texts in English. Although students found it useful, its implementation should be regulated to ensure that it does not cause excessive dependence on the original language. In summary, translanguaging can serve as an effective approach to improve learners' comprehension by giving them the opportunity to utilize all they language resource.